Variability in the serial interval of COVID-19 in South Korea: a comprehensive analysis of age and regional influences - Lee, Hyosun; Lee, Gira; Kim, Tobhin; Kim, Suhyeon; Kim, Hyoeun; Lee, Sunmi (Frontiers in Public Health, 2024)
Quantifying the transmissibility over time by region and age using parameters such as serial interval and time-varying reproduction number, and understanding the impact of geographical factors on transmission, are crucial for formulating effective disease control strategies. Due to the dedicated work of epidemiologists in South Korea, it has become possible to construct a large dataset of infected individuals, including symptom onset dates, allowing for detailed analysis with a focus on age and regional parameters. During this period, the COVID-19 pandemic is divided into four distinct phases, taking into account characteristics such as suppression policies, emergence of variants, and vaccination. We evaluate epidemic control policies by visualizing various interventions such as social distancing, vaccination, school closure policies, and population density, quantifying the age and region-specific spread trends using parameters like serial interval, heatmap, and time-varying reproduction number. Analyzing transmission pairs over time within age groups reveals a significant impact of school closure policies on the spread among individuals aged 0-19. Additionally, it allows us to infer transmission events occurring in parent-child and teacher-student relationships. Considering the population of each age group and region, changes in confirmed cases over time indicate a reduction in the spread among those aged 65 and older with a high vaccination rate, while densely populated metropolitan areas show an increase in the scale of confirmed cases. Furthermore, investigating time-varying reproduction numbers by region reveals heterogeneity in the spread across different areas.Regions implementing strict social distancing measures, such as the metropolitan area, showed an increase in confirmed cases, but also a delayed spread, indicating the effectiveness of epidemic control policies. Our study emphasizes the evaluation of effective epidemic control policies by quantifying key parameters of COVID-19, including social distancing, school closure policies, and vaccine impact.